The Relationship between Limb Muscle Explosive Power and Volleyball Blocking Skills in Extracurricular at Dehasen University Bengkulu - Meldi Hartono; Feby Elra Perdima; Deffri Anggara (Hanoman Journal: Physical Education and Sport, 2021)
This study aims to determine the relationship between limb muscle explosive power and blocking skills in volleyball athletes in Dehasen Bengkulu. This research is a quantitative correlational study using a correlation test which aims to determine the relationship between the independent variable and the dependent variable. The population in this study were all Dehasen Bengkulu volleyball athletes, totaling 35 people. The sample used is as many as 19 people. The correlation coefficient of leg muscle explosive power on volleyball athletes' blocking skills of 0.9239 is positive, meaning that the greater the score obtained, the stronger the relationship between the two variables. The significance test of the correlation coefficient was carried out by means of the value of rcount with rtable at = 5% with N=19 obtained rtable of 0.456. Because the correlation coefficient between rx.y = 0.9239 r(0.5)(19) = 0.456, it means that the relationship between limb muscle explosive power and blocking skills is significant.